The financial economics of privatization - Megginson, William L. (New York : Oxford University Press, 2005)
The focus of this book lies on where privatization stands today and what are the next frontiers, the why and how behind countries who privatize certain industries, whether privatization works as an economic tool and important insights relevant to financial institutions such as how to value privatized industries, how share offerings differ from private offerings, and how countries go about harnessing private capital. The book will also represent a key and unique source for information related to the details of asset sales privatization, a summary of statistics of privatized companies from 54 international stock exchanges, regulatory changes and sources for privatization information for investors, government officials, bankers and financial specialists. The volume will serve as an invaluable reference for professionals and as a core or supplementary text in privatization courses.
The scope of privatization -- Why do countries privatize? -- How do countries privatize? -- Empirical evidence on privatization's effectiveness in non-transition economies -- Empirical evidence on privatization in transition economies -- The structure and investment performance of privatization share offerings -- Privatization's impact on financial market development -- Privatization industry studies: telecommunications -- Privatization industry studies: commercial banking -- Privatization industry studies: energy and airlines -- The lessons and future of privatization.
Includes bibliographical references and index.
rpm 03/05/13
Loans
Keywords: Privatization; Government business enterprises; Finance, Public